Ultraendurance triathlon participation: typical race preparation of lower level triathletes - Gulbin, J. P.; Gaffney, P. T. (The Journal of Sports Medicine and Physical Fitness, 1999)
BACKGROUND: This study sought to describe the training preparations and performances of lower level ultraendurance triatheletes. The lower level or typical ultraendurance athlete was defined as any participant eligible to compete, irrespective of ability. METHODS: Experimental design: participants completed a retrospective questionnaire related to their athletic background, triathlon experience and performances, and training preparation. Setting: all competitors in the 1995 Lanzarote Ironman (i.m.) triathlon had the opportunity to complete the questionnaire in the days prior to the race. Participants: 242 (230 m, 12 f) or 45% of the entire race field completed the questionnaire. Measures: measures of central tendency were used to describe all data. Forward step-wise multiple regression techniques were used to predict performance from training variables. Statistical significance was accepted at p < 0.05. RESULTS: Mean finish time for all study participants was 11.76 hours. Subjects were 34.2 +/- 8.8 years, 1.77 +/- 0.07 m, and 70.8 +/- 7.1 kg. They had 6.0 +/- 3.2 years experience in triathlon, had completed 3.0 +/- 4.1 IM races, and spent 21.5 +/- 10.8 weeks preparing for the IM. Training distances/week for swimming, cycling and running, were 8.8 +/- 4.3 km, 270 +/- 107 km, and 58.2 +/- 21.9 km, at a pace of 18.1 min/km, 31.8 km/hr, and 4.55 min/km respectively. Previous best performances in Olympic distance triathlon (1.5/40/10) coupled with weekly cycling distances and longest training ride, could partially predict overall performance (R2 = 0.57). CONCLUSIONS: Finishing an IM requires less training than has been previously reported in studies that have primarily focused on elite competitors. Additionally, training distances appear to be a more important factor for competitive success than training paces.